Effect of Storage Temperature Change on Freshness of Shell Eggs - Dehui CHEN; Huanxing DU; Shanhai LI; Qin LEI; Jing ZHANG; Haijun CHANG; Yan DAI (Shipin gongye ke-ji, 2023)
This research investigated egg freshness of Roman pink in 4 storage temperature change groups. The shell eggs were storage for 0, 10, 20, 30 d, and weight loss, gas chamber height, Haugh unit, yolk index, thick-to-thin albumen ratio and albumen pH of all shell egg experiment groups were evaluated. The results showed that weight loss increased significantly (P<0.05), whereas gas chamber height and thick-to-thin albumen ratio decreased significantly (P<0.05) in shell eggs of treatment group 2, group 3 and group 4. The pH of all experiment group eggs (except control group) firstly increased and then decreased. The significant decrease (P<0.05) of yolk index was detected in eggs of treatment group 3 and group 4. The Haugh unit, yolk index and thick-to-thin albumen ratio in control and treatment group 1 shell eggs were significantly higher than that of treatment group 3 and group 4. The pH of treatment group 2 shell eggs, stored for 10~20 days, was significant (P<0.05) higher than that of control and treatment group 1. Therefore, the shell eggs stored for first 10 days at ambient temperature (≥20 ℃), showed significant increase of weight loss and decrease of Haugh unit. The results of this study indicate that the freshness of the shell eggs following storage temperature change treatments is more prone to deterioration compared with that of low temperature storage (4 ℃).